O cânone em transcendência: Homoerotismo em Retrato de rapaz, de Mário Cláudio - Barili, Renan Augusto (2018)
In the present work, certain aspects of the novel Retrato de Rapaz (2014), by the Portuguese writer Mário Cláudio, were analyzed, through the biases of homoeroticism and historiographical metafiction, in order to reflect on the figuration of Leonardo da Vinci, transformed into a fictional character in this novel. The central idea was to discuss the processes of revisiting and reconstructing sacred figures, starting with questions about sexuality as a form of resistance and breaking with certain pre-established heteronormative concepts. In doing so, can we not transcend the image of the Renaissance artist, since, with this fable, it allows one to think about the occurrence of a possible “hygiene” imposed on History, which relegated, to a second level, all these sexualities that were disengaged from a normative logic? As the novel and the trajectory of the Italian artist teach us, we can no longer live in times that subject certain subjectivities to a marginalized plane, since differences and diversities require experiencing visibility and respect.